Comparative Risk Analysis of Two Culicoides‐Borne Diseases in Horses: Equine Encephalosis More Likely to Enter France than African Horse Sickness. Issue 6 (23rd September 2016) - Faverjon, C.; Leblond, A.; Lecollinet, S.; Bødker, R.; de Koeijer, A. A.; Fischer, E. A. J.
Summary: African horse sickness (AHS) and equine encephalosis (EE) are Culicoides ‐borne viral diseases that could have the potential to spread across Europe if introduced, thus being potential threats for the European equine industry. Both share similar epidemiology, transmission patterns and geographical distribution. Using stochastic spatiotemporal models of virus entry, we assessed and compared the probabilities of both viruses entering France via two pathways: importation of live‐infected animals or importation of infected vectors. Analyses were performed for three consecutive years (2010–2012). Seasonal and regional differences in virus entry probabilities were the same for both diseases. However, the probability of EE entry was much higher than the probability of AHS entry. Interestingly, the most likely entry route differed between AHS and EE: AHS has a higher probability to enter through an infected vector and EE has a higher probability to enter through an infectious host. Consequently, different effective protective measures were identified by 'what‐if' scenarios for the two diseases. The implementation of vector protection on all animals (equine and bovine) coming from low‐risk regions before their importation was the most effective in reducing the probability of AHS entry. On the other hand, the most significant reduction in the probability of EE entry was obtained by the implementation of quarantine before import for horses coming from both EU and non‐EU countries. The developed models can be useful to implement risk‐based surveillance.